A study on the problems encountered by organisations in the implementation of Quality Management System ISO 9001:2000 in construction industry. (case study location: Klang Valley area, N. Sembilan, Melaka and Johore - 2 site - visits per location) / Abdul Rahman Ayub and Janidah Eman - Ayub, Abdul Rahman; Eman, Janidah (2006)
In Malaysia, misunderstanding among organization on Quality Management System (QMS) concept is an obstacle for its implementation in all management system in this industry. Thus, organization should understand some elements in QMS to overcome this problem such as the philosophy, concepts and procedures. QMS design and implementation are influenced by the needs, objectives, process and structure. Usually, these are different depending on the organizations’ policy. Therefore, the deep understanding and guidance of QMS can improve the effectiveness in the implementation of QMS by organization in the Malaysia Construction Industry. The objectives of this research are to study the scenario of QMS application, to identify the problems encountered by organization and to issue recommendation on how to improve the implementation of QMS in Malaysia Construction Industry. The scope of this study focuses in the organization in the Center region area. The organization can be divided by top, medium and lower level management. This research is obtained and finalized by the reading and distribution of the 150 samples of questionnaires mainly to the top, medium and lower level management. From the data analysis by the SPSS program, the findings of the study shows most of respondents in Construction Industry has a high level awareness with the scenario of QMS application, the common problems encountered by organization and recommendation to improve the QMS implementation problems occurred in Malaysia Construction Industry is identify.